Biopsychosocial Factors Affecting Quality of Life in Post-stroke Patients: A Path Analysis Evidence from Surakarta Hospital, Central Java - Zamzam, Maki; Tamtomo, Didik Gunawan; Widyaningsih, Vitri (Journal of Epidemiology and Public Health, 2020)
Background: Basic health research shows that the prevalence of non-communicable diseases has in